Faith in the Digital Age: The Impact of Religious Influencers on Followers’ Religious Engagement - Latif, Alfa Taufan; Kuntoro, Diadji (Innovative: Journal Of Social Science Research, 2025)
This study examines how followers derive meaning from religious influencer content and its significance in their daily lives. The research aims to identify the role of religious influencers in shaping religious practices and follower behavior. The subjects of this study are followers of religious influencers on social media, with data collection conducted through in-depth interviews and content analysis. The results indicate that religious influencers, such as Ustaz Hanan Attaki, serve as modern conduits for religious teachings, leading to the formation of new religious practices among their followers. Despite their substantial influence, the appeal of merchandise associated with these influencers remains limited. It can be concluded that religious influencers have a significant impact on shaping religious understanding and practices among their followers.